Work-Life Balance as a Mediator Between Work Environment and Psychological Well-Being Among University Lecturers and Administrative Staff - Turuk, Gilbert Pieter De Vendy; Wijaya, R Pasifikus Christa; Riwu, Audrey Gracelia; Handoyo, Nicholas Edwin (Malaysian Journal of Medical Sciences, 2026)
Background: This study examined the direct and indirect effects of the work environment on psychological well-being (PWB), with work-life balance (WLB) as a mediating variable among lecturers and administrative staff at Universitas Nusa Cendana, Indonesia.Methods: A cross-sectional quantitative survey was conducted in June 2025 across several faculties and administrative units using validated Indonesian versions of three instruments: the 32-item Work Environment Services Scale, the 15-item WLB Scale, and the 18-item Ryff PWB Scale. A total of 347 respondents participated, comprising 229 lecturers and 118 administrative staff. Data were analysed using SmartPLS 4.0 and PROCESS Macro Model 4 with 5,000 bootstrap resamples.Result: A total of 347 respondents were included in the analysis. PWB was significantly impacted directly by the work environment (β = 0.20, P < 0.001). WLB accounted for 54.4% of the total effect and significantly mediated the association between PWB and the work environment (indirect effect β = 0.24, P < 0.001). The model explained 25.3% of the variance in WLB and 39.2% of the variance in PWB, suggesting a significant role for WLB in the relationship between workplace conditions and employee well-being.Conclusion: A supportive work environment enhances PWB directly and indirectly through WLB. Strengthening collegial relationships, equitable workload distribution, and WLB-based policies can effectively promote staff well-being in higher education, particularly in eastern Indonesia.